Personality Congruence Among Brands, Recruiters, and Applicants During the Anticipatory Socialization Process. (November 2019) - Kang, Alice Yeonjung; Legendre, Tiffany S.; Cartier, Elizabeth A.
Drawing on congruence theory, this study aims to examine the impact of internal brand management, perceived level of job opportunities, and their interaction effects on job applicants during the anticipatory socialization process in the hospitality industry. Data were collected from students and job seekers in the hospitality industry with qualitative (focus group interview) and quantitative approaches (2 × 2 and 2 × 2 × 2 between-subjects quasi-experimental design). The findings indicate that recruiters who receive internal brand management have a positive impact on applicants' congruence perception toward the brand. Furthermore, this effect becomes stronger when candidates perceive employment opportunities as abundant, which increases job attraction and job pursuit intentions.